Electronic and Magnetic Investigations of Rare-Earth Tm-doped AlGaN Ternary Alloy - Belhachi, S.; Lazreg, Abbassia; Dridi, Z.; Al-Douri, Yarub (Springer Verlag, 2018)
Electronic structure and magnetic interaction of substitutional thulium rare earth-doped wurtzite Al0.5Ga0.5N ternary alloy have been performed using density-functional theory within local spin-density approximation with Hubbard-U corrections (LSDA+U) approach. The LSDA+U method is applied to the rare earth (RE) 4f states. The calculation of formation energy shows that it is more energetically favorable for a substitutional Tm atom to replace the Al atom than the Ga atom. For AlGaN:Tm, the lattices parameters are expanded due to larger ionic radius of Tm than that of Al atoms. The energy band gap of AlGaN:Tm has direct character and its width becomes small compared with that of AlGaN. The magnetic coupling between Tm ions in the nearest neighbor sites is ferromagnetic. Magnetic interaction of rare earth ion with the host states at the valence and conduction band edges has been investigated and compared to those of GaN:Mn and has been found to be relatively small.